Biochemical perspective of gingival crevicular fluid: a diagnostic tool for the detection of periodontal health and diseases – a systematic review. - Ravi, Dr. Dinesh Kumar; Shunmugavelu, Karthik; Vijayaselvam, Bincy Sharon (Student's Journal of Health Research Africa, 2026)
Background: Periodontal diseases remain a major global oral health problem and a principal cause of tooth loss. Conventional diagnostic methods such as probing depth, bleeding on probing, clinical attachment level, and radiographic evaluation primarily indicate previous tissue destruction rather than current disease activity. Gingival crevicular fluid (GCF), a site-specific biofluid present in the gingival sulcus, contains host-derived and microbial molecules associated with periodontal inflammation and tissue breakdown. These components may serve as measurable indicators of active periodontal pathology. Materials and Methods: Electronic databases (PubMed/MEDLINE, Scopus, Embase, LILACS, and Web of Science) were searched for studies published between 2020 and 2024 using keywords related to gingival crevicular fluid, periodontal disease, biomarkers, and diagnosis. The review followed PRISMA recommendations. After applying eligibility criteria, five studies were included. Data extraction covered study design, geographic location, evaluated biomarkers, and diagnostic findings. Methodological quality was assessed using the STROBE checklist. Results: Included studies reported several host-derived biomarkers in GCF associated with periodontal inflammation and tissue destruction. Matrix metalloproteinase-8 (MMP-8), tartrate-resistant acid phosphatase (TRAP-5), osteoprotegerin (OPG), inflammatory cytokines and related enzymatic markers demonstrated the ability to differentiate periodontal health from varying severities of periodontitis. These markers correspond to inflammatory signaling, connective tissue degradation, and bone remodeling. Conclusion: GCF offers a non-invasive medium for assessing molecular changes within periodontal tissues. Biomarkers related to inflammation, matrix degradation and bone metabolism may assist in identifying disease activity and monitoring progression. Variability in sampling procedures and analytical techniques currently limits routine clinical application, indicating the need for standardized longitudinal investigations.